A study on the implementation of dual career at European higher education institutions: the student-athletes' and experts' views - Izzicupo, Pascal; Serafini, Sofia; Prestanti, Iris; Fusco, Andrea; Abalasei, Beatrice-Aurelia; Alonso del Hierro, Tara; Çalışkan, Burak; Di Baldassarre, Angela; Ege, Håkon; Figueiredo, Antonio J.; Ghinassi, Barbara; González-García, Higinio; et al. (Frontiers in Sports and Active Living, 2025)
IntroductionThe holistic development of elite athletes is a priority within European sports policies, necessitating a coordinated approach to dual career support. This study evaluated the perspectives of both university experts and student-athletes (S-As) on various dual career aspects, aiming to provide actionable insights for improving policies within European higher education institutions (HEIs).Materials and methodsData was collected through an online survey tailored for HEI experts and S-As across multiple countries. A total of 46 HEI experts and 321 S-As responded to the survey. The role of the country of origin on each dual career aspect for S-As was investigated using a MANOVA, followed by an ANOVA and post hoc analyses using Tukey's test when an effect emerged. The data from HEI experts and comparisons between S-As and HEI experts were handled descriptively due to the violation of assumptions of homogeneity of variances and sufficient sample size.ResultsThe study revealed significant trends and disparities in the availability and quality of support services. In particular, logistic, and financial support, and other support/policies areas showed a significant effect for S-As countries of origin, with Romanian and Serbian S-As generally reporting better scores and Italian and Spanish worse. In general, HEI experts rated dual career provision areas more favorably than S-As.ConclusionThis study underscores the importance of integrating both HEI expert and S-As' perspectives to develop effective dual career policies. Tailored interventions and enhanced communication about available resources are crucial for improving the dual career experiences of S-As across Europe.